Yarning With Country: An Indigenist Research Methodology. (March 2021) - Hughes, Margaret; Barlo, Stuart
In this article, we invite you into conversation about Yarning with Country. We contemplate the question: How do we work within a relational methodology with Country as a primary participant? We are interested in the practice of relating intentionally with Country: the ontological orientation and visceral receptivity which is required. This contemplation includes considering how we exist in relationship with Country, how we learn from and with Country, and how we cultivate respectful, reciprocal, and accountable relationships with Country. We choose to share this process with you as a conversation between people and with Country because that is the way this kind of sharing takes place: in person, in real time, in Place, between beings. Our contention in this article is that human beings would benefit from a more engaged, communicative relationship with Country; we suggest that this requires honing our skills of listening, respecting, sharing, and letting be.